NonLTE ANALYSIS OF THE NaI LINES IN THE SOLAR SPECTRUM - Ivanova, D. V.; Shimansky, V. V. (Одеські астрономічні публікації, 2017)
Solar spectrum of Nal lines by method of the nonLTE analysis is investigated. It shown, that in atmosphere of the Sun the Nal is in moderate ”overrecombination”. The analysis of influence of atomic data, models of atmospheres and damping constants for nonLTE deviation and sodium abundances is made. Observational solar spectrum of strong lines Nal has been synthesized in good approximation. On summary data of 15 lines the sodium abundance is determined:-5.78dex.